Metode Talqin Ibn Sina Dalam Pembelajaran Agama Islam Melalui Asmaul Husna Di Tk Cempaka Mulya 1 Pilangrejo Demak - Khondziroh, kiki Luluk; ., Taufikin (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
This study examines the application of the Talqin Ibnu Sina method in teaching Asmaul Husna at TK Cempaka Mulya 1 Pilangrejo Demak, with a focus on the routine of reciting Asmaul Husna every morning. This habituation aims to introduce and internalize Islamic values in students, while also shaping positive character traits such as akhlakul karimah, solidarity, and social care. The Talqin Ibnu Sina method is implemented by having teachers recite Asmaul Husna, which is then followed by the students together each morning. This practice enhances their memory and encourages the application of these values in daily life. The findings of the study show that the application of this method has a positive impact on students' social, emotional, and character development, making them more virtuous, with an Islamic personality, and capable of socializing effectively. The routine of reciting Asmaul Husna has proven to be effective in establishing a foundation of Islamic values in children.